Patronyme, frontière et identité ethnique dans le Mayo-Louti : essai d’analyse onomastique des anthroponymes et de leur origine tribale dans la ville de Figuil (Cameroun) - Warayanssa Mawoune (OpenEdition, 2020)
This paper examines the identity anchoring of surnames within the ethnic groups present in Figuil in Northen Cameroon. An onomastic and ethnolinguistic analysis, based on seventy-six surnames, determines the attribution system of surnames as it is practiced within families and the disparity that sometimes exists between these names and the ethnic origins of individuals.